Peningkatan Keaktifan Lembaga Sosial Lokal untuk Mengatasi Kenakalan Remaja di Wilayah Pedesaan - Muhammad Fauzan (Universitas Mathla'ul Anwar Banten, 2021)
INCREASING THE ACTIVITY OF LOCAL SOCIAL INSTITUTIONS TO REDUCE JUVENIL DELINQUENCY IN RURAL AREAS. The economic improvement of the community in Temuwuh Village along with the development of the home-based wooden handicraft turned out to create a number of social problems. These problems occurred due to economic improvement that was not accompanied by increasing in the quality of human resources, especially the younger generation. These problems were: 1) the emergence of various juvenile delinquency, 2) decreasing number of adolescents to continue higher education despite being economically capable, 3) the lack of local institutions social activity, and 4) the lack of participation by the youth in the local social activities. The general objectives of the Community Service Program were (1) increase the activity of local social institutions, especially those based on religion and cultural arts, so they become more positive and guided, (2) improve knowledge and role of the community to identify the potential of their adolescents, and (3) provide character education for adolescents in particular and all members of society in general. To achieve these targets according to the existing problems, a number of activities have been done including: 1) Socialization and counseling of youth potential and character education with counseling, religious studies, and intensive discussion, 2) Skills training for local social institutions with a) training gamelan for karawitan groups and b) training in reading the Qur'an and Islamic art for TPA groups, and 3) Assistance for local social group activities with a) intensive discussion and b) green walk.